2019
DOI: 10.18632/aging.102319
|View full text |Cite
|
Sign up to set email alerts
|

Systematic profiling of alternative splicing events and splicing factors in left- and right-sided colon cancer

Abstract: Left- and right-sided colon cancer (LC and RC) differ substantially in their molecular characteristics and prognoses, and are thus treated using different strategies. We systematically analyzed alternative splicing (AS) events and splicing factors in LC and RC. RNA-seq data were used for genome-wide profiling of AS events that could distinguish LC from RC. The Exon Skip splicing pattern was more common in RC, while the Retained Intron pattern was more common in LC. The AS events that were upregulated in RC wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
(61 reference statements)
0
25
0
Order By: Relevance
“…The OS of patients with stage II-III CRC is affected by many factors besides tumor stage, such as tumor location, histological type, age, sex, microsatellite status, and RAS/RAF mutation, and no single factor can accurately predict survival in CRC. 8,9 In addition, sophisticated and expensive laboratory techniques have limits to their application. Nomograms have been widely used in clinical oncology as reliable tools for estimating numerical probabilities for individual patients by incorporating and illustrating important prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OS of patients with stage II-III CRC is affected by many factors besides tumor stage, such as tumor location, histological type, age, sex, microsatellite status, and RAS/RAF mutation, and no single factor can accurately predict survival in CRC. 8,9 In addition, sophisticated and expensive laboratory techniques have limits to their application. Nomograms have been widely used in clinical oncology as reliable tools for estimating numerical probabilities for individual patients by incorporating and illustrating important prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with CRC can vary greatly, even within the same TNM stage. The OS of patients with stage II‐III CRC is affected by many factors besides tumor stage, such as tumor location, histological type, age, sex, microsatellite status, and RAS/RAF mutation, and no single factor can accurately predict survival in CRC . In addition, sophisticated and expensive laboratory techniques have limits to their application.…”
Section: Introductionmentioning
confidence: 99%
“…AS, as a post-transcriptional regulatory process that modifies more than 90% of human genes, plays a significant role in enhancing the diversity of transcription and protein (9,12,13). In recent years, the dysregulation of AS has been found to be associated with the occurrence and development of a variety of cancers including NSCLC (26)(27)(28)(29)(30)(31)(32). For instance, Li et al profiled the genome-wide AS events of NSCLC from TCGA and constructed prognostic predictors for LUAD, LUSC and merged NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, cancer-specific AS events have been identified by comparing cancer tissues with normal controls in several studies. And associations between AS signatures and overall survival (OS) time of patients have been systematically evaluated in a variety of cancers, such as colorectal cancer, ovarian cancer, breast cancer, kidney renal clear cell carcinoma, esophageal carcinoma as well as NSCLC (26)(27)(28)(29)(30)(31)(32). However, although systematic analysis and prognostic prediction models of AS events for NSCLC have been conducted in some studies, no comprehensive study specifically for LUSC has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Flodrops et al [ 31 ] found that TIMP1 intron 3 retention could affect the progression of colon cancer. Huang et al [ 32 ] constructed an AS signature based on differentially expressed AS events between left- and right-sided colon cancer. In the present study, we detected eleven AS events for the construction of the model.…”
Section: Discussionmentioning
confidence: 99%